Pancreatic duct occlusion with polychloroprene-based glue for the management of postoperative pancreatic fistula after pancreatoduodenectomy—an outdated approach? - Yaqub, Sheraz; Røsok, Bård; Gladhaug, Ivar Prydz; Labori, Knut Jørgen (Frontiers in Surgery, 2024)
Managing postoperative pancreatic fistula (POPF) presents a challenge after pancreatoduodenectomy. Some centers consider pancreatic duct occlusion (PDO) in reoperations following pancreatoduodenectomy as a pancreas-preserving procedure, aiming to control a severe POPF. The aim of this study was to evaluate the short- and long-term outcomes of employing PDO for the management of the pancreatic stump during relaparotomy. Retrospective review of consecutive patients at Oslo University Hospital undergoing pancreatoduodenectomy and PDO during relaparotomy. Pancreatic stump management consisted of occlusion of the main pancreatic duct with polychloroprene Faxan-Latex, after resecting the dehiscent jejunal loop previously constituting the pancreaticojejunostomy. Between July 2005 and September 2015, 826 pancreatoduodenectomies were performed. Overall reoperation rate was 13.5% (n=109). POPF grade B/C developed in 113 (13.7%) patients. PDO during relaparotomy was performed in 17 (2.1%) patients, whereas completion pancreatectomy was performed in 22 (2.7%) patients. Thirteen (76%) of the 17 patients had a persistent POPF after PDO, and the time from PDO until removal of the last abdominal drain was median 35 days. Of the PDO patients, 13 (76%) patients required further drainage procedures (n=12) or an additional reoperation (n=1). In-hospital mortality occurred in one patient (6%). Five (29%) patients developed new-onset diabetes mellitus, and 12 (94%) patients acquired exocrine pancreatic insufficiency. PDO is a feasible approach for managing severe POPF during reoperation following pancreatoduodenectomy. A significant proportion of patients experience persistent POPF, necessitating supplementary drainage interventions. The findings suggest that it is advisable to explore alternative pancreas-preserving methods before opting for PDO in the management of POPF.